Multiple Adverse Effects of Systemic Corticosteroids: A Case Report - Divya Satyanarayanasetty (Journal of Clinical and Diagnostic Research, 2015)
Corticosteroids are among the effective treatments available for many medical conditions. Adverse effects such as osteoporosis, cataract and muscle weakness are widely recognized on long term administration and have considerable public health implications. Many reports are available that have dealt with individual adverse effects.Here, we report a case of a 55-year-old female, with systemic glucocorticoid induced bilateral cataract, osteoporosis, diabetes mellitus and hypothalamic pituitary axis (HPA) suppression. These were induced through self –medication. She presented to the hospital for the treatment of acute exacerbation of bronchial asthma.